2019
DOI: 10.1186/s12906-019-2582-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cervical carcinoma effect of Portulaca oleracea L. polysaccharides by oral administration on intestinal dendritic cells

Abstract: Background Cervical cancer is the second most prevalent cancer worldwide. Portulaca oleracea L. polysaccharide (POL-P3b) has been found to have enhancing immune and anti-cervical cancer activity by oral administration. Dendritic cells (DC) play a key roles in regulating intestinal immune homeostasis. In this study, we analyzed the inhibition apoptosis effects of POL-P3b on intestinal DC and relevant mechanisms. Methods Intestinal DC was isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity in rat ovarian and gastric cancer and mouse cervical cancer and sarcomas, as shown Table 2 [19][20][21][22]62]. Another bioactivity from P. oleracea is portulacacerebrosie A, a cerebroside compound that suppresses the invasion and metastasis of liver cancer HCCLM3 cells and acts in leucocythemia treatment are show in Table 2 [24,63].…”
Section: Bioactive Compounds Of P Oleracea On Anticancer Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative Medicine and Cellular Longevity in rat ovarian and gastric cancer and mouse cervical cancer and sarcomas, as shown Table 2 [19][20][21][22]62]. Another bioactivity from P. oleracea is portulacacerebrosie A, a cerebroside compound that suppresses the invasion and metastasis of liver cancer HCCLM3 cells and acts in leucocythemia treatment are show in Table 2 [24,63].…”
Section: Bioactive Compounds Of P Oleracea On Anticancer Activitymentioning
confidence: 99%
“…Polysaccharides from P. oleracea act on free radicals through the antioxidant mechanism, modulating the immune system, which may be preventive and therapeutic in rat ovarian and gastric cancer and mouse cervical cancer and sarcomas, as shown Table 2 [ 19 22 , 62 ].…”
Section: Bioactive Compounds Of P Oleracea On Anti...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Portulaca oleracea L . polysaccharides (POL‐P3b), derived from the monodentate plant, demonstrated tumor growth inhibition and immunoregulation, and can be used for treating cervical cancer and for enhancing immunity 83,105 . As a biologic response regulator, polysaccharides promote cellular humoral and immune responses to inhibit and eliminate tumor cells.…”
Section: Molecular Mechanisms On Natural Products In Tumor Immunotherapymentioning
confidence: 99%
“…Additionally, POL‐P3b can also induce apoptosis of intestinal DC by stimulating the TLR4‐PI3K/AKT‐NF‐κB signaling pathway. In vivo studies have shown that POL‐P3b possess a significant inhibitory effect on cervical cancer xenografts 105 . Xie's group reported the immunoregulatory activity of the polysaccharide from Gganoderma atrum (PGA) in CT26 and S180 tumor‐burdened mouse models, as evidenced by the activation of macrophage phagocytosis and inhibition of tumor growth by PGA through the inhibition of the MAPK signal pathway, induced by TLR4 101,102 .…”
Section: Molecular Mechanisms On Natural Products In Tumor Immunotherapymentioning
confidence: 99%